Antacid provides better restoration of glandular structures within the gastric ulcer scar than omeprazole. Issue 7 (July 1994) - Schmassmann, A; Tarnawski, A; Gerber, H A; Flogerzi, B; Sanner, M; Varga, L; Halter, F
Abstract : Mucosa of healed gastric ulcers displays histological abnormalities that are possibly the basis of ulcer recurrence. The influence of antacid and omeprazole treatment was studied on the quality of ulcer healing. Sixty four rats with gastric cryoulcers were treated daily either with placebo, antacid, omeprazole, or antacid plus omeprazole. Ulcer size was measured three times per week with a novel video endoscopic method. Prostaglandin generation (day 6), cell proliferation (day 8 and 15), height and cell composition of ulcer margin (day 8), and mucosal scar (day 15) were quantitatively assessed. Antacid, omeprazole, and antacid plus omeprazole significantly accelerated ulcer healing predominantly during days 3-8. Compared with placebo, the height of ulcer margin and mucosal ulcer scar was significantly increased in antacid (+7 and +9% respectively) and significantly decreased in omeprazole (-33 and -22% respectively) and antacid plus omeprazole (-26 and -18% respectively) treated rats. The number of bromodeoxyuridine labelled cells (+42%, day 8), epithelial cell mass (+42%, day 15), and the ratios of epithelial cells/connective tissue (+73%, day 15) and epithelial cells/gland lumen (+100%, day 15) were significantly increased in antacid treated rats. In conclusion, both antacid and omeprazole accelerate ulcer healing but antacid provides a better quality of healing. This advantage is lost by cotreatment with omeprazole.